TATA IBADAH TERHADAP KUALITAS KEROHANIAN PARA ANGGOTA FULL GOSPEL BUSINESS MEN’S FELLOWSHIP INTERNATIONAL (LITURGY TO THE SPIRITUALITY QUALITY OF FULL GOSPEL BUSINESS MEN'S FELLOWSHIP INTERNATIONAL MEMBERS) - Leo Immanuel (QUAERENS: Journal of Theology and Christianity Studies, 2019)
This study aims to test, find out and prove empirically about the effect of effective worship practices on the spiritual quality of FGBMFI members in the Ancol Fishermen Chapter, North Jakarta. The population in this study are all members of the FGBMFI Chapter Ancol Fishermen, North Jakarta with a total of 100 people. The research sample of 80 people taken using simple random sampling technique. The results of data analysis show that: There is an effect of the effectiveness of worship procedures on the quality of spirituality. The test results showed a correlation coefficient of 0.296 and with a calculated coefficient of 2.742 with a P-value of 0.008. Increasing the effectiveness of worship procedures will have an impact on improving the quality of spirituality. Penelitian ini bertujuan untuk menguji, mengetahui dan membuktikan secara empiris tentang pengaruh efektifitas tata ibadah terhadap kualitas kerohanian para anggota FGBMFI di Chapter Nelayan Ancol, Jakarta Utara. Populasi dalam penelitian ini adalah semua anggota member yang ada di FGBMFI Chapter Nelayan Ancol, Jakarta Utara dengan jumlah sebanyak 100 orang. Sampel penelitian sebanyak 80 orang yang diambil dengan menggunakan teknik simple random sampling. Hasil analisis data menunjukan bahwa: Terdapat pengaruh efektifitas tata ibadah terhadap kualitas kerohanian. Hasil pengujian menunjukkan koefisisen korelasi sebesar 0,296 dan dengan koefisien t-hitung sebesar 2,742 dengan P–value sebesar 0,008. Meningkatkan efektifitas tata ibadah akan berdampak terhadap peningkatan kualitas kerohanian.